Protective Effect of Melatonin for Renal Ischemia-Reperfusion Injury: A Systematic Review and Meta-Analysis - Dun, Rong-liang; Lan, Tian-ying; Tsai, Jennifer; Mao, Jian-min; Shao, Yi-qun; Hu, Xiao-hua; Zhu, Wen-jing; Qi, Guang-chong; Peng, Yu (Frontiers in Physiology, 2022)
Background: Renal ischemia-reperfusion (I/R) injury is one of the major causes related to acute kidney damage. Melatonin has been shown as a powerful antioxidant, with many animal experiments have been designed to evaluate the therapeutic effect of it to renal I/R injury. Objectives: This systematic review aimed to assess the therapeutic effect of melatonin for renal I/R injury in animal models. Methods and Results: The PubMed, Web of Science, Embase, and Science Direct were searched for animal experiments applying melatonin to treat renal I/R injury to February 2021. Thirty-one studies were included. The pooled analysis showed a greater reduction of blood urea nitrogen (BUN) (21 studies, weighted mean difference (WMD) = −30.00 [−42.09 to −17.91], p < 0.00001), and serum creatinine (SCr) (20 studies, WMD = −0.91 [−1.17 to −0.66], p < 0.00001) treated with melatonin. Subgroup analysis suggested that multiple administration could reduce the BUN compared with control. Malondialdehyde and myeloperoxidase were significantly reduced, meanwhile, melatonin significantly improved the activity of glutathione, as well as superoxide dismutase. The possible mechanism for melatonin to treat renal I/R injury is inhibiting endoplasmic reticulum stress, apoptosis, inflammation, autophagy, and fibrillation in AKI to chronic kidney disease. Conclusions: From the available data of small animal studies, this systematic review demonstrated that melatonin could improve renal function and antioxidative effects to cure renal I/R injury through, then multiple administration of melatonin might be more appropriate. Nonetheless, extensive basic experiments are need to study the mechanism of melatonin, then well-designed randomized controlled trials to explore the protective effect of melatonin.